Case Report: Primary segmental volvulus in an infant - Wang, Wenya; Jiang, Xiaoping; Wu, Weilu; Zhang, Li (Frontiers in Pediatrics, 2025)
Primary segmental volvulus (PSV) is a rare cause of acute abdomen in infants. It is characterized by a form of strangulated intestinal obstruction requiring prompt diagnosis and surgical intervention. This study aimed to report a case of PSV in an infant, which was managed successfully through early recognition, close clinical monitoring, and timely surgical treatment. Although both blood and ascitic fluid cultures were negative postoperatively, metagenomic next-generation sequencing (mNGS) identified the same pathogen in both specimens, enabling targeted antibiotic therapy. This case highlights the importance of including PSV in the differential diagnosis of infants presenting with unexplained abdominal distension and bilious vomiting, particularly when accompanied by anemia. Additionally, the elevated level of the coagulation system biomarker thrombin–antithrombin complex (TAT) may serve as a useful marker for monitoring coagulation status in the perioperative period. The integration of TAT assessment and mNGS-based pathogen identification provides a novel framework for individualized perioperative management in PSV.